Green Gold in Peril: How the Mexican Cartels Threaten the Michoacan Avocado Production - Manullang, Abel Josafat; Khairunnisa, Najwa Dzakkiyah; Sudirman, Arfin (Jurnal Studi Sosial dan Politik, 2023)
The avocado industry has been an important piece in Mexico’s economy. Known as the “green gold”, most avocados are produced in Michoacan, the most suitable region in Mexico to grow them. The avocado industry also brings huge benefits like the avocado boom that has created countless jobs in Mexico. However, the Michoacan avocado production has been the target of the cartels as they seek to gain control over them. Through the use of qualitative research methods, the article seeks to explain the ways cartels pose a threat to the Michoacan avocado production, the reason behind the cartels entry to the industry, the bleak prospects if they are left unhandled including how the governments can take care of it. The article finds that the cartels threaten Michoacan avocado production through its violent measures as its means to gain control of it. The motivation behind the cartels’ race to control the industry can be pointed to Mexico’s political development and the industry’s exponential boom. Moreover, the urgency for the government’s decisive action is explained through the bleak prospects brought by the cartels which range from deterioration of Mexico’s national institution to economic repercussions. The article ends with elaboration on the ways the government can respond to the issue which could be done through the act of securitization and cooperating with other states, notably the US as the biggest buyer of avocados from Michocan and Mexico’s neighbor.